Livestock policies for the Caribbean. - WALMSLEY, Don (1995)
Discusses the conclusions and recommendations of the regional seminar held in Port-of-Spain, Trinidad and Tobago, in March 1995. The seminar examined the existing livestock sector, defined a regional policy and identified priority areas for implementation.